PENGARUH ROE, DAR, REPUTASI KANTOR AKUNTAN PUBLIK (KAP) TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2011-2014 - Ruslinda Agustina; Nur Khalimah (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2016)
Abstract,This research aims to determine the effect of ROE, DAR, the reputation of the Public Accounting Firm (KAP) to the timeliness of financial reports on companies listed on the Stock Exchange.The method used in this research is purposive sampling method, from a population of 153 companies listed on the Stock Exchange were taken 40 companies that meet the criteria of a sample that has a complete report from 2011 to 2014. Testing hipotesis done using logistic regression analysis was tested by assessing the feasibility linier regression model, assess the model summary and test coefficient regression model with the help of SPSS version 16.The partial results of hypothesis testing showed that the ROE, DAR, and the reputation of the Public Accounting Firm (KAP) does not significantly influence the timeliness of financial reports, while simultaneously ROE, DAR and reputation Public Accounting Firm (KAP) significantly affect the timeliness of financial reports.